Hashtag (#) as Message Identity in Virtual Community - Mulyadi, Urip; Fitriana, Lisa (Universitas Semarang, 2018)
Computer Mediated Communication or CMC is able to present a virtual community, where the people inside have the same interest to share information related to events, activities, competitions, entertainment, history, event and others in Semarang City for publication. This research attempted to describe that hashtags can be utilized as the identity of a message in a communications network on Facebook Group MIK Semar. The results of this study are hashtags have changed how we build a virtual community, as the use of hashtags in Facebook Group MIK SEMAR as message identity to build better relationship and support communication among its members.